Impacts of soil erosion on ecosystem provisioning services: Oddo Shakiso District, Guji Zone, Oromia, Ethiopia - Teshome Deresse; Tsegu Ereso; Erko Geremu (Cogent Arts & Humanities, 2023)
AbstractEcosystem services are vital for the well-being of all life on the earth’s surface. However, soil loss resulting from soil erosion affects ecosystem services and societal well-being, which is a difficulty facing humans currently. Though the main objectives of the study were to assess the impacts of soil erosion on the provision of food and fresh water services in Odo Shakiso district, The sequential explanatory research design was employed to identify the impacts of soil erosion, and questionnaires were distributed to 309 households with two site residents, and key informant discussions were held with ten individuals selected from organizations. Binary logistic regression would be used to analyze the relationships and effects among variables. At Odo Shakiso, the soil erosion is equated with the statistics of potential slight erosion type, which has the prime change, and the result shows soil loss has high significant impacts on the productivity of land, availability of water, and fuel wood access (p < 0.01) and has significant effects on land use (p < 0.05). A common considerate effect of soil erosion on ecosystem provisioning services and these linked interactions is essential to making sound decisions, and our results could also help to intervene in the policy of sustainable land management and soil conservation decisions to mount future human socioeconomic and environmental quality. Therefore, before this great abode of diverse ecosystem services and the all-over existence of the surrounding communities’ soil are gradually devastated, decisive measures need to be taken by the concerned stakeholders.